Water-soluble polymer, preparation method thereof and application of water-soluble polymer in composition for grinding
By preparing water-soluble polymers with controllable molecular weight and sulfonic acid end groups, the problem of uncontrollable molecular weight of water-soluble polymers in the prior art is solved, its performance and application value in the polishing process are improved, and polysilicon is realized /Efficient polishing effect of silicon nitride.
Patent Information
- Application Number
- CN202411363693.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-28
- Publication Date
- 2024-12-27
AI Technical Summary
The molecular weight of existing water-soluble polymers is uncontrollable during the synthesis process, which is difficult to meet the specific needs of the fine chemical industry for controllable molecular weight and end-group structure. Especially in the polishing process in integrated circuit manufacturing, the polycrystalline silicon/silicon nitride selection ratio needs to be improved. and reduce the residue on the polysilicon surface.
By selecting suitable polymer monomers and functional group modification methods, water-soluble polymers with controllable molecular weight and sulfonic acid end groups are prepared, and the molecular weight and end group structure of the polymer are regulated by polymerization and reducing oxidation reactions to improve their molecular weight and end group structure. Solubility and functionality in water.
The polymer has a narrow molecular weight distribution, high physical property stability and good solubility, and the polishing rate selection ratio of polycrystalline silicon/silicon nitride is improved, product defects are reduced, and the polishing effect of the polishing composition is significantly improved.
Smart Images

Figure CN119192444A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of water-soluble polymers, and in particular to a water-soluble polymer with a controllable molecular weight and a sulfonic acid end group, a preparation method thereof, and an application thereof in a grinding composition. Background Art
[0002] Water-soluble polymers have hydrophilic / lipophilic amphiphilic properties and can be used as surfactants in personal care products, chemicals, food, medicine, and high-end semiconductor industries. Water-soluble polymers are usually synthesized by free radical polymerization, but the water-soluble polymers obtained by this polymerization method have problems such as uncontrollable molecular weight and wide molecular weight distribution. With the demand for refinement of water-soluble polymers in recent years, there is an urgent need to find water-soluble polymers with controllable molecular weight, specific end group structure and function.
[0003] In integrated circuit manufacturing, the entire silicon wafer is generally flattened by chemical mechanical polishing. In the polishing process of polysilicon, it is generally required to remove polysilicon at a higher polishing rate, and silicon nitride is used as a stop layer, so it is necessary to increase the polysilicon / silicon nitride selectivity; in addition, in order to reduce the residue on the surface of polysilicon, it is necessary to add an organic component with good water solubility and strong ability to wrap the polishing residue to the polishing composition. Summary of the invention
[0004] The purpose of the embodiments of the present application is to provide a water-soluble polymer and a preparation method thereof, and the application thereof in a grinding composition. The water-soluble polymer and the preparation method thereof in the embodiments of the present application can select suitable polymerization monomers as needed to prepare polymers with different functionalities, and then improve the solubility and functionality of the polymer through a functional group modification method to obtain a water-soluble polymer with a controllable molecular weight and a sulfonic acid end group to meet different application requirements.
[0005] In the first aspect, the present application provides a water-soluble polymer with controllable molecular weight and a sulfonic acid end group, characterized in that its general structural formula is as follows:
[0006] Wherein, R1 is at least one of hydrogen, cyanoethyl, isobutyl cyano; R2 and R3 are each independently at least one of alkyl, alkoxy, ester, carboxylic acid, amide, and aromatic ring; n is any natural number. Preferably, the molecular weight of the water-soluble polymer is in the range of 800-2000.
[0007] In the above technical solution, the water-soluble polymer has a narrow molecular weight distribution, and thus has a higher physical property stability, and the water-soluble polymer has a sulfonic acid end group, which can improve its solubility in water.
[0008] In a possible implementation, at least one of R2 and R3 has at least one of a methacrylate group, an acrylate group, a styrene group and a pyrrolidone group. Preferably, at least one of R2 and R3 has a pyrrolidone group.
[0009] In a possible implementation, the water-soluble polymer is obtained by polymerizing a solution consisting of a polymerization monomer, a chain transfer agent, an initiator and a solvent at a first preset temperature and a first preset time; then adding a reducing agent to carry out a reduction reaction, reacting at a second preset temperature and a second preset time; and then adding an oxidant to carry out an oxidation reaction;
[0010] Wherein, the first preset temperature and the second preset temperature are both in the range of 60°C-120°C, and the first preset time and the second preset time are both in the range of 6h-12h.
[0011] In a possible implementation, both R2 and R3 are derived from the polymerized monomer, and the general structural formula of the polymerized monomer is The R1 comes from the chain transfer agent, and the general structural formula of the chain transfer agent is Wherein, Z is at least one of an alkyl group, an aryl group, an aralkyl group, a sulfanyl group, an alkoxy group, an aryloxy group, and an amino group; after the polymerization reaction is completed, a first polymer is obtained, and the general structural formula of the first polymer is The initiator is a free radical polymerization thermal initiator, including but not limited to an organic peroxide initiator, an azo initiator and a redox initiator.
[0012] In a possible implementation, the molar ratio of the polymerization monomer, the chain transfer agent and the initiator is 100:1:0.1-100:20:10.
[0013] In a possible implementation, after the reduction reaction is completed, a second polymer is obtained, and the general structural formula of the second polymer is The molar ratio of the reducing agent to the solvent is 10:1-100:1.
[0014] In a possible implementation, the molar ratio of the oxidant to the chain transfer agent is 10:1-100:1.
[0015] In a second aspect, the present application provides a method for preparing a water-soluble polymer with a controllable molecular weight and a sulfonic acid end group, the preparation method comprising the following steps:
[0016] S1: A solution consisting of a polymerizable monomer, a chain transfer agent, an initiator and a solvent undergoes a polymerization reaction at a first preset temperature and within a first preset time;
[0017] S2: adding a reducing agent, and reacting at a second preset temperature and within a second preset time;
[0018] S3: adding an oxidant to obtain the water-soluble polymer according to any one of the implementation modes of the first aspect;
[0019] Wherein, the general structural formula of the chain transfer agent is Z is at least one of an alkyl group, an aryl group, an aralkyl group, a sulfanyl group, an alkoxy group, an aryloxy group, and an amino group; R1 is at least one of a hydrogen group, a cyanoethyl group, and an isobutylcyano group; the general structural formula of the polymerizable monomer is: R2 and R3 are each independently at least one of an alkyl group, an alkoxy group, an ester group, a carboxylic acid, an amide, and an aromatic ring. The first preset temperature and the second preset temperature are both in the range of 60-120°C. The first preset time and the second preset time are both in the range of 6-12h.
[0020] In the above technical scheme, a water-soluble polymer with controllable molecular weight and terminal sulfonic acid group is obtained by polymerization method and functional group modification method in sequence. In the polymerization reaction, the molecular weight and molecular weight distribution of the polymer can be controlled by adjusting the reaction conditions; and then by the functional group modification method, the terminal group of the polymer is adjusted to sulfonic acid group by using reducing agent and oxidizing agent, because sulfonic acid group has good hydrophilicity, so as to improve the solubility of the polymer in water.
[0021] In a possible implementation, at least one of R2 and R3 has at least one of a methacrylate group, an acrylate group, a styrene group and a pyrrolidone group.
[0022] In a possible implementation, in the step S1, the molar ratio of the polymerization monomer, the chain transfer agent and the initiator is 100:1:0.1-100:20:10.
[0023] In a possible implementation, in the step S2, the molar ratio of the reducing agent to the solvent is 10:1-100:1.
[0024] In a possible implementation, in the step S3, the molar ratio of the oxidant to the chain transfer agent is 10:1-100:1.
[0025] In a third aspect, the present application provides a grinding composition comprising abrasive particles, water, a pH regulator, and a water-soluble polymer as described in any one of the implementations of the first aspect.
[0026] In the above technical solution, by adding the above water-soluble polymer to the polishing composition, the polishing rate selectivity of polysilicon / silicon nitride is increased, while product defects are reduced, so that the polishing effect of the polishing composition is significantly improved. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0028] It should be noted that the following embodiments are examples of the present application and are only used to illustrate the present application, but not to limit the present application. Other combinations and various improvements within the concept of the present application may be made without departing from the subject matter or scope of the present application.
[0029] The water-soluble polymer with controllable molecular weight and sulfonic acid end groups provided in the present application, its preparation method, and grinding composition are described in detail below.
[0030] The general structural formula of the water-soluble polymer in the embodiment of the present application is as follows:
[0031]
[0032] In the above general structural formula, R1 is at least one of hydrogen, cyanoethyl, and isobutylcyano; R2 and R3 are each independently at least one of alkyl, alkoxy, ester, carboxylic acid, amide, and aromatic ring; and n is any natural number.
[0033] The molecular weight of the water-soluble polymer in the embodiment of the present application can be any value, preferably in the range of 800-2000, such as 800, 1100, 1600, 2000, etc. The water-soluble polymer has a narrow molecular weight distribution, so it has high physical stability, and the water-soluble polymer has a sulfonic acid end group, which can improve its solubility in water.
[0034] The preparation method of the water-soluble polymer of the embodiment of the present application comprises the following steps:
[0035] S1: A solution consisting of a polymerizable monomer, a chain transfer agent, an initiator and a solvent undergoes a polymerization reaction at a first preset temperature and within a first preset time; wherein the general structural formula of the chain transfer agent is Z is at least one of an alkyl group, an aryl group, an aralkyl group, a sulfanyl group, an alkoxy group, an aryloxy group, and an amino group, and R1 is at least one of a hydrogen group, a cyanoethyl group, and an isobutylcyano group.
[0036] The general structural formula of the polymerized monomer is R2 and R3 are independently at least one of an alkyl group, an alkoxy group, an ester group, a carboxylic acid, an amide, and an aromatic ring. The first preset temperature ranges from 60 to 120° C., and the first preset time ranges from 6 to 12 hours.
[0037] S2: Add a reducing agent and react at a second preset temperature and a second preset time; the second preset temperature ranges from 60 to 120° C., and the second preset time ranges from 6 to 12 hours.
[0038] S3: Add an oxidizing agent to obtain the above-mentioned water-soluble polymer.
[0039] Specifically, in step S1, a chain transfer agent and an initiator are added to a reaction bottle, nitrogen is replaced three times, and then a polymerization monomer and a solvent are added, and after the chain transfer agent and the initiator are dissolved, nitrogen is replaced three times, and then slowly heated to a first preset temperature under a nitrogen atmosphere, and the polymerization time under the nitrogen atmosphere is maintained for the first preset time. After the reaction is completed, the temperature is lowered and the nitrogen protection is removed, and the reaction is stirred for 1 hour under an air atmosphere to quench free radicals. Among them, the first preset temperature is usually between 60°C and 100°C, such as 60°C, 70°C, 80°C, 100°C, etc.; the first preset time is usually between 6h and 10h, such as 6h, 8h, 10h, etc.
[0040] In step S2, a reducing agent is added, and then the reaction is refluxed at a second preset temperature for a second preset time. After the reaction is completed, most of the solvent is removed by rotary evaporation or the reducing agent is removed by filtering or other means to obtain a precipitate. The second preset temperature is usually between 80°C and 120°C, such as 80°C, 100°C, 120°C, etc.; the first preset time is usually between 6h and 10h, such as 6h, 8h, 10h, etc.
[0041] In step S3, the precipitate is dissolved and then an oxidant is added. After the oxidation is completed, the oxidant is removed and then the water-soluble polymer with sulfonic acid terminal groups is collected.
[0042] The present application sequentially obtains a water-soluble polymer with a controllable molecular weight and a sulfonic acid end group through a polymerization method and a functional group modification method. In the polymerization reaction, the molecular weight and molecular weight distribution of the polymer can be controlled by adjusting the reaction conditions (such as temperature, time, chain transfer agent, and initiator content, etc.) to achieve a controllable molecular weight of the water-soluble polymer. Then, through a functional group modification method, a reducing agent and an oxidizing agent are used to adjust the end group of the polymer to a sulfonic acid group, because the sulfonic acid group has good hydrophilicity, so as to improve the solubility of the polymer in water.
[0043] Due to the wide range of applicable polymerization monomers, different types of polymers with different functionalities can be prepared, and then the terminal groups can be modified through specific methods to improve the solubility and functionality of the polymers to meet different application requirements and improve the use value of the polymers. This allows us to select appropriate polymerization monomers as needed in practical applications to prepare the required polymers, achieve the adjustment of polymer structure and performance, and expand its application in the field of fine chemicals.
[0044] In a possible implementation, R2 and R3 are both derived from polymerized monomers, and the general structural formula of the polymerized monomers is At least one of R2 and R3 has at least one of a methacrylate group, an acrylate group, a styrene group and a pyrrolidone group, that is, the functional group of the polymerized monomer is selected from the functional groups of methacrylate, acrylate, styrene and pyrrolidone. Preferably, at least one of R2 and R3 has a pyrrolidone group.
[0045] Specific examples of the polymerizable monomers that can be used in the present application are listed below, but are not limited to these examples. For example, methyl methacrylate, ethyl methacrylate, propyl methacrylate (all isomers), butyl methacrylate (all isomers), 2-ethylhexyl methacrylate, isobornyl methacrylate, methacrylic acid, benzyl methacrylate, phenyl methacrylate, methacrylonitrile, α-methylstyrene, acrylic acid, methyl acrylate, ethyl acrylate, propyl acrylate (all isomers), butyl acrylate (all isomers), 2-ethylhexyl acrylate, isobornyl acrylate, benzyl acrylate, phenyl acrylate, acrylonitrile, styrene, glycidyl methacrylate, benzophenone methacrylate, 3,4-epoxy methacrylate, Cyclohexyl methyl ester, 3,4-epoxycyclohexyl methyl acrylate, 2-hydroxyethyl methacrylate, hydroxypropyl methacrylate (all isomers), hydroxybutyl methacrylate (all isomers), N,N-dimethylaminoethyl methacrylate, N,N-diethylaminoethyl methacrylate, triethylene glycol methacrylate, itaconic anhydride, itaconic acid, glycidyl acrylate, 2-hydroxyethyl acrylate, hydroxypropyl acrylate (all isomers), hydroxybutyl acrylate (all isomers), N,N-dimethylaminoethyl acrylate, N,N-diethylaminoethyl acrylate, triethylene glycol acrylate, acrylamide, methacrylamide, N-methylacrylamide, N,N-Dimethylacrylamide, N-tert-butylmethacrylamide, N-n-butylmethacrylamide, N-hydroxymethylmethacrylamide, N-hydroxyethylmethacrylamide, N-tert-butylacrylamide, N-n-butylacrylamide, N-hydroxymethylacrylamide, N-hydroxyethylacrylamide, vinylbenzoic acid (all isomers), diethylaminostyrene (all isomers), α-methylvinylbenzoic acid (all isomers), diethylaminoα-methylstyrene (all isomers), p-vinylbenzenesulfonic acid, p-vinylbenzenesulfonic acid sodium salt, trimethoxysilylpropyl methacrylate, triethoxysilylpropyl methacrylate, tributoxysilylpropyl methacrylate, dimethoxymethylsilylpropyl methacrylate, diethoxymethylsilylpropyl methacrylate, dibutoxymethylsilylpropyl methacrylate, diisopropoxymethylsilylpropyl methacrylate, dimethoxysilylpropyl methacrylate, methyl Diethoxysilylpropyl acrylate, dibutoxysilylpropyl methacrylate, diisopropoxysilylpropyl methacrylate, trimethoxysilylpropyl acrylate, triethoxysilylpropyl acrylate, tributoxysilylpropyl acrylate, dimethoxymethylsilylpropyl acrylate, diethoxymethylsilylpropyl acrylate, dibutoxymethylsilylpropyl acrylate, diisopropoxymethylsilylpropyl acrylate, dimethoxysilylpropyl acrylate, diethoxysilylpropyl acrylate, dibutoxysilylpropyl acrylate, diisopropoxysilylpropyl acrylate; vinyl acetate, vinyl butyrate, vinyl benzoate, vinyl chloride, vinyl fluoride, vinyl bromide, maleic anhydride, N-phenylmaleimide, N-butylmaleimide, N-vinyl pyrrolidone, N-vinyl carbazole, butadiene, ethylene and chloroprene, mixtures of these monomers, and mixtures of these monomers with other monomers. ,
[0046] Preferably, the polymerizable monomer is selected from one or more of methyl methacrylate (A-1), butyl methacrylate (A-2), acrylic acid (A-3), vinyl acetate (A-4), N-vinyl pyrrolidone (A-5), acrylamide (A-6), N-isopropyl acrylamide (A-7), dimethyl allylamine (A-8), acrylonitrile (A-9), styrene (A-10), p-sulfonic acid styrene (A-11), and N-vinyl carbazole (A-12), and the specific structure is as follows:
[0047]
[0048] The polymerizable monomers may also have other functional groups, and none of the functional groups reacts during the polymerization reaction.
[0049] In a possible implementation, R1 comes from a chain transfer agent, and the general structural formula of the chain transfer agent is Wherein, Z is at least one of an alkyl group, an aryl group, an aralkyl group, a sulfanyl group, an alkoxy group, an aryloxy group, and an amino group. The chain transfer agent includes dithioesters, trithiocarbonates, dithiocarbamates, and xanthates.
[0050] Specific examples of chain transfer agents that can be used in the present application are listed below, but are not limited to these examples. For example, 4-morpholine dithiocarboxylic acid cyanoethyl ester, O-ethyl (1-phenylethyl) dithiocarbonate, 2-ethyl xanthogenyl isobutyric acid, 3-tert-butyl-1-ethyl thiodicarbonate, phenyl dithioic acid, benzyl dithiobenzoate, 2-phenyl-2-propyl benzodisulfide, 2-methyl-2-propyl benzodithiolate, 2-cyanopropyl-2-yl benzodisulfide, 2-(thiobenzoylthio) propionic acid, dibenzyl trithiocarbonate, cyanomethyl-N-methyl (4-pyridine) aminodithiocarboxylate, 2-(dodecylthiocarbonylthiothio)-2-methyl 3-Butenyl propionate, 4-cyano-4-[(dodecylsulfanylthiocarbonyl)sulfanyl]pentanoic acid, 4-cyano-4-[(dodecylsulfanylthiocarbonyl)sulfanyl]pentanol, dodecyl cyanomethyl trithiocarbonate, [3-(trimethoxysilyl)propyl] cyanomethyl trithiocarbonate, dodecyl 2-cyano-2-propyl trithiocarbonate, S,S-dibenzyl trithiocarbonate, 2-(dodecylthiocarbonylthiothio)-2-methylpropionic acid, 2-(dodecylthiocarbonylthiothio)-2-methylpropionic acid 3-azido-1-propanol ester;, 2-(dodecylthiocarbonylthiothio)-2-methylpropionic acid N-hydroxysuccinimide ester, 2-(dodecylthiocarbonylthiothio)-2-methylpropionic acid pentafluorophenyl ester, 2-(dodecylthiocarbonylthiothio) propionic acid, 2-(dodecylthiocarbonylthiothio)-2-methylpropionic acid methyl ester, pentaerythritol tetrakis[2-(dodecylthiocarbonylthiothio)-2-methylpropionic acid ester], butyl trithiocarbonic acid phthalimidomethyl ester, 1,1,1-trithiocarbonyl (dodecylthiocarbonylthiothio)-2-methylpropionate] ethane, benzyl 1H-pyrrole-1-dithiocarbamate, diphenyl dithiocarbamate cyanomethyl ester, methyl (phenyl) dithiocarbamate cyanomethyl ester, methyl (4-pyridyl) dithiocarbamate cyanomethyl ester, N-methyl-N-(pyridin-4-yl) dithiocarbamate 2-cyanopropane-2-yl ester, 2-[methyl (4-pyridinyl) carbamoylthiothio] propionate, 1-succinimidyl-4-cyano 4-[N-methyl-N-(4-pyridyl)carbamoylthiothio]pentanoate, benzyl benzodithiocarboxylate, cyanomethyl benzodithiocarboxylate, 4-cyano-4-(phenylcarbonylthiothio)pentanoic acid, 4-cyano-4-(phenylcarbonylthiothio)pentanoic acid N-succinimidyl ester, 2-cyano-2-propyl benzodithiocarboxylate, 2-cyano-2-propyl 4-cyanobenzodithiocarboxylate, ethyl 2-(4-methoxyphenylcarbonylthiothio)acetate, 2-methyl -2-(phenylthiocarbonylthio)propionic acid ethyl ester, 2-(phenylcarbonylthiothio)-2-phenylethyl ester, 2-(phenylcarbonylthiothio)propionic acid ethyl ester, 1-(methoxycarbonyl)ethyl benzodithioate, 2-(4-methoxyphenylcarbonylthiothio)acetic acid, 4-cyano-4-(phenylcarbonylthiothio)pentanoic acid 2-nitro-5-(2-propynyloxy)benzyl ester, 2-(phenylcarbonylthiothio)propionic acid, 2-phenyl-2-propyl benzodithioate. ;
[0051] Preferably, the chain transfer agent is selected from one or more of 4-morpholine dithiocarboxylic acid cyanoethyl ester (C-1), O-ethyl (1-phenylethyl) dithiocarbonate (C-2), 2-ethylxanthogenic isobutyric acid (C-3), 3-tert-butyl-1-ethyl thiodicarbonate (C-4), phenyl dithioic acid (C-5), benzyl dithiobenzoate (C-6), 2-phenyl-2-propylbenzodisulfide (C-7), 2-methyl-2-propylbenzodithiolate (C-8), 2-cyanopropyl-2-ylbenzodisulfide (C-9), 2-(thiobenzoylthio) propionic acid (C-10), dibenzyl trithiocarbonate (C-11), and cyanomethyl-N-methyl (4-pyridine) aminodithiocarboxylate (C-12), and the specific structure is as follows:
[0052]
[0053] The initiator is a free radical polymerization thermal initiator, including but not limited to an organic peroxide initiator, an azo initiator and a redox initiator. Specific examples of initiators that can be used in the present application are listed below, but are not limited to these examples. For example, 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2-cyanobutane), dimethyl 2,2'-azobis(isobutyrate), 4,4'-azobis(4-cyanovaleric acid), 1,1'-azobis(cyclohexanenitrile), 2-(tert-butylazo)-2-cyanopropane, 2,2'-azobis{2-methyl-N-[1,1-bis(hydroxymethyl)-2- 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide], 2,2'-azobis(N,N'-dimethyleneisobutyramidine) dihydrochloride, 2,2'-azobis(2-amidinopropane) dihydrochloride, 2,2'-azobis(N,N'-dimethyleneisobutyramidine), 2,2'-azobis{2-methyl-N-[1,1-bis(hydroxymethyl) -2-hydroxyethyl] propionamide}, 2,2'-azobis{2-methyl-N-[1,1-bis(hydroxymethyl)-2-ethyl] propionamide}, 2,2'-azobis[2-methyl-N-(2-hydroxyethyl) propionamide], 2,2'-azobis(isobutylamide) dihydrate, 2,2'-azobis(2,2,4-trimethylpentane), 2,2'-azobis(2-methylpropane), tert-butyl peroxyacetate, tert-butyl peroxybenzoate, tert-butyl peroxyneodecanoate, tert-butyl peroxyisobutyrate, tert-amyl peroxypivalate, tert-butyl peroxypivalate, diisopropyl peroxydicarbonate, dicyclohexyl peroxydicarbonate, dicumyl peroxide, dibenzoyl peroxide, dilauroyl peroxide, potassium peroxydisulfate, ammonium peroxydisulfate, di-tert-butyl dinitrate, diisopropyl dinitrate.
[0054] When selecting a free radical polymerization thermal initiator, the selected initiator needs to have a suitable half-life at the first preset temperature to achieve sufficient activity within the first preset time. Preferably, azo initiators include azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, azobisisobutylamidine hydrochloride, etc.; peroxide initiators include hydrogen peroxide, ammonium persulfate, potassium persulfate, benzoyl peroxide, tert-butyl benzoyl peroxide, methyl ethyl ketone peroxide, etc.; redox initiators include dibenzoyl peroxide (BPO) and N,N-dimethylaniline (DMA).
[0055] Optionally, the initiator may also be a photochemical initiator. When selecting a photochemical initiator, the selected initiator needs to meet the required free radical generation rate at a first preset temperature and a first preset time, such as benzoin derivatives, benzophenone, acylphosphine oxide and photoredox system.
[0056] In step S1, the polymerization monomer, chain transfer agent and initiator undergo polymerization reaction in a solvent, and the solvent can be one, two or a mixture of more than two common solvents such as ethyl acetate, butanone (MEK), acetonitrile, ethanol, methanol, propanol, toluene, tetrahydrofuran, dioxane, N,N-dimethylformamide, N,N-dimethylacetamide, N,N-diethylformamide, N,N-diethylacetamide, dimethyl sulfoxide, etc.
[0057] After the above polymerization reaction is completed, a first polymer is obtained, and the general structural formula of the first polymer is In step S1, the specific process is as follows:
[0058]
[0059] In a possible implementation, the molar ratio of the polymerization monomer, the chain transfer agent and the initiator is 100:1:0.1-100:20:10. Specifically, the molar ratio of the polymerization monomer, the chain transfer agent and the initiator can be 100:1:0.1, 100:1:1, 100:10:0.1, 100:10:10, 100:20:10, etc.
[0060] In a possible implementation, in step S2, after the reduction reaction is completed, a second polymer is obtained, and the general structural formula of the second polymer is The specific process is as follows:
[0061]
[0062] The reducing agent may be sodium borohydride, sodium cyanoborohydride, diisobutylaluminum hydride, lithium aluminum hydride, hydrazine hydrate, etc. The molar ratio of the reducing agent to the solvent in step S1 is 10:1-100:1, specifically 10:1, 30:1, 60:1, 100:1, etc.
[0063] In a possible implementation, in step S3, after the oxidation reaction is completed, the water-soluble polymer is obtained. The specific process is as follows:
[0064]
[0065] The oxidant may be hydrogen peroxide, peracetic acid, potassium dichromate, chromic acid, sodium hypochlorite, potassium permanganate, etc. The molar ratio of the oxidant to the chain transfer agent in step S1 is 10:1-100:1, specifically 10:1, 30:1, 60:1, 100:1, etc.
[0066] The water-soluble polymer provided in the present application can be applied in a grinding composition. The present application also provides a grinding composition, comprising abrasive particles, water, a pH regulator, and a water-soluble polymer of any one of the above implementations. Since the surface of silicon nitride is positively charged, the water-soluble polymer having a sulfonic acid end group can be electrostatically adsorbed on the surface of silicon nitride, thereby achieving the polishing of silicon nitride during the polishing process, thereby improving the polishing rate selectivity of polysilicon / silicon nitride.
[0067] The abrasive particles can be one or more of silicon dioxide, aluminum oxide, zirconium dioxide, cerium oxide, silicon carbide, iron oxide, titanium dioxide, silicon nitride, preferably silicon dioxide. The particle size of the abrasive particles is preferably 30-200nm. The content of the abrasive particles is preferably 0.5-20%, and the percentage is mass percentage.
[0068] The pH adjuster can be an organic base or an inorganic base, such as aqueous ammonia, potassium hydroxide, sodium hydroxide, sodium methoxide, sodium ethoxide, triethylamine, triethanolamine, etc. The pH adjustment range is preferably between 8 and 11.
[0069] The water is preferably deionized water.
[0070] The above and other advantages of the present invention may be better understood through the following examples, but the following examples are not intended to limit the scope of the present invention.
[0071] Example 1
[0072] S1: Chain transfer agent cyanomethyl-N-methyl (4-pyridine) aminodithiocarboxylate (C-12, 12mmol, 2.791g) and free radical initiator azobisisobutyronitrile (AIBN, 1.25mmol, 205mg) were added to the reaction bottle, and then nitrogen was replaced three times. Then, solvent dioxane (33mL) and polymerization monomer N-vinylpyrrolidone (A-5, 125mmol, 13.36g) were added, and nitrogen was replaced three times. After that, it was heated to 70°C under nitrogen atmosphere. The polymerization time was 7h. After the reaction was completed, the temperature was lowered and the nitrogen protection was removed. It was stirred for 1h under air atmosphere to quench the free radicals.
[0073] S2: The polymer synthesized above is dissolved in a solvent having a volume ratio of 1:2 of dioxane and hydrazine hydrate, and then refluxed at 100°C for 8 hours. After the reaction is completed, most of the dioxane and ammonia water are removed by rotary evaporation, and then the mixture is heated and dried under an oil pump for 3 hours to remove the residual hydrazine hydrate.
[0074] S3: Add 50 ml of 30% hydrogen peroxide to the polymer from which hydrazine hydrate has been removed, dissolve it by ultrasonication, and remove the hydrogen peroxide using a freeze dryer. The final yield is about 80%.
[0075] Molecular weight determination: The molecular weight of the water-soluble polymer was determined to be 800 and the molecular weight distribution (PDI) was 1.068 using a room temperature gel permeation chromatography (GPC) apparatus (Agilent 1260) (manufactured by Agilent Technologies, Inc.) and a column (PLgei 5μm MIXED-C 300*7.5mm) (manufactured by Agilent Technologies, Inc.). Column temperature: 50°C, eluent: water, flow rate: 1.0 ml / min, standard sample for calibration curve preparation: polyethylene glycol. The molecular weight of the water-soluble polymer was determined to be 800 and the molecular weight distribution (PDI) was 1.068.
[0076] Example 2
[0077] S1: Chain transfer agent cyanomethyl-N-methyl (4-pyridine) aminodithiocarboxylate (C-12, 10mmol, 2.233g) and free radical initiator azobisisobutyronitrile (AIBN, 1.25mmol, 205mg) were added to the reaction bottle, and then replaced with nitrogen three times. Then, solvent dioxane (33mL) and polymerization monomer N-vinylpyrrolidone (A-5, 125mmol, 13.36g) were added, and nitrogen was replaced three times. After that, it was heated to 70°C under nitrogen atmosphere. The polymerization time was 7h. After the reaction was completed, the temperature was lowered and the nitrogen protection was removed. It was stirred for 1h under air atmosphere to quench the free radicals.
[0078] S2: The polymer synthesized above is dissolved in a solvent having a volume ratio of 1:2 of dioxane and hydrazine hydrate, and then refluxed at 100°C for 8 hours. After the reaction is completed, most of the dioxane and ammonia water are removed by rotary evaporation, and then the mixture is heated and dried under an oil pump for 3 hours to remove the residual hydrazine hydrate.
[0079] S3: Add 50 ml of 30% hydrogen peroxide to the polymer from which hydrazine hydrate has been removed, dissolve it by ultrasonication, and remove the hydrogen peroxide using a freeze dryer. The final yield is about 80%.
[0080] Molecular weight determination: The molecular weight of the water-soluble polymer was determined to be 1100 and the molecular weight distribution (PDI) was 1.083 using a room temperature gel permeation chromatography (GPC) apparatus (Agilent 1260) (manufactured by Agilent Technologies, Inc.) and a column (PLgei 5μm MIXED-C 300*7.5mm) (manufactured by Agilent Technologies, Inc.). Column temperature: 50°C, eluent: water, flow rate: 1.0 ml / min, standard sample for calibration curve preparation: polyethylene glycol. The molecular weight of the water-soluble polymer was determined to be 1100 and the molecular weight distribution (PDI) was 1.083.
[0081] Example 3
[0082] S1: Chain transfer agent cyanomethyl-N-methyl (4-pyridine) aminodithiocarboxylate (C-12, 10mmol, 2.233g) and free radical initiator azobisisobutyronitrile (AIBN, 1.25mmol, 205mg) were added to the reaction bottle, and then nitrogen was replaced three times. Then, solvent dioxane (33mL) and polymerization monomer methyl methacrylate (A-1, 125mmol, 12.51g) were added, and nitrogen was replaced three times. After that, it was heated to 70°C under nitrogen atmosphere. The polymerization time was 7h. During the polymerization process, the polymerization system gradually changed from light yellow to reddish brown. After the reaction was completed, the temperature was lowered and the nitrogen protection was removed. Stir for 1h in air atmosphere to quench the free radicals.
[0083] S2: The polymer synthesized above is dissolved in a solvent having a volume ratio of 1:2 of dioxane and hydrazine hydrate, and then refluxed at 100°C for 8 hours. After the reaction is completed, most of the dioxane and ammonia water are removed by rotary evaporation, and then the mixture is heated and dried under an oil pump for 3 hours to remove the residual hydrazine hydrate.
[0084] S3: Add 50 ml of 30% hydrogen peroxide to the polymer from which hydrazine hydrate has been removed, dissolve it by ultrasonication, and remove the hydrogen peroxide using a freeze dryer. The final yield is about 83%.
[0085] Molecular weight determination: The molecular weight of the water-soluble polymer was determined to be 1180 and the molecular weight distribution (PDI) was 1.062 using a room temperature gel permeation chromatography (GPC) apparatus (Agilent 1260) (manufactured by Agilent Technologies, Inc.) and a column (PLgei 5μm MIXED-C 300*7.5mm) (manufactured by Agilent Technologies, Inc.). Column temperature: 50°C, eluent: water, flow rate: 1.0 ml / min, standard sample for preparing the calibration curve: polyethylene glycol. The molecular weight of the water-soluble polymer was determined to be 1180 and the molecular weight distribution (PDI) was 1.062.
[0086] Example 4
[0087] S1: Chain transfer agent cyanomethyl-N-methyl (4-pyridine) aminodithiocarboxylate (C-12, 10mmol, 2.233g) and free radical initiator azobisisobutyronitrile (AIBN, 1.25mmol, 205mg) were added to the reaction bottle, and then nitrogen was replaced three times. Then, solvent dioxane (33mL) and polymerization monomer acrylamide (A-6, 125mmol, 8.88g) were added, and nitrogen was replaced three times. After that, it was heated to 70°C under nitrogen atmosphere. The polymerization time was 7h. After the reaction was completed, the temperature was lowered and the nitrogen protection was removed. It was stirred for 1h under air atmosphere to quench the free radicals.
[0088] S2: The polymer synthesized above is dissolved in a solvent having a volume ratio of 1:2 of dioxane and hydrazine hydrate, and then refluxed at 100°C for 8 hours. After the reaction is completed, most of the dioxane and ammonia water are removed by rotary evaporation, and then the mixture is heated and dried under an oil pump for 3 hours to remove the residual hydrazine hydrate.
[0089] S3: Add 50 ml of 30% hydrogen peroxide to the polymer from which hydrazine hydrate has been removed, dissolve it by ultrasonication, and remove the hydrogen peroxide using a freeze dryer. The final yield is about 85%.
[0090] Molecular weight determination: The molecular weight of the water-soluble polymer was determined to be 1250 and the molecular weight distribution (PDI) was 1.075 using a room temperature gel permeation chromatography (GPC) apparatus (Agilent 1260) (manufactured by Agilent Technologies, Inc.) and a column (PLgei 5μm MIXED-C 300*7.5mm) (manufactured by Agilent Technologies, Inc.). Column temperature: 50°C, eluent: water, flow rate: 1.0 ml / min, standard sample for preparing the calibration curve: polyethylene glycol. The molecular weight of the water-soluble polymer was determined to be 1250 and the molecular weight distribution (PDI) was 1.075.
[0091] Example 5
[0092] S1: Chain transfer agent cyanomethyl-N-methyl (4-pyridine) aminodithiocarboxylate (C-12, 10mmol, 2.233g) and free radical initiator azobisisobutyronitrile (AIBN, 1.25mmol, 205mg) were added to the reaction bottle, and then replaced with nitrogen three times. Then, solvent dioxane (33mL) and polymerization monomer p-styrene sulfonate (A-11, 125mmol, 23.02g) were added, and nitrogen was replaced three times. After that, it was heated to 70°C under nitrogen atmosphere. The polymerization time was 7h. After the reaction was completed, the temperature was lowered and the nitrogen protection was removed. It was stirred for 1h under air atmosphere to quench the free radicals.
[0093] S2: The polymer synthesized above is dissolved in a solvent having a volume ratio of 1:2 of dioxane and hydrazine hydrate, and then refluxed at 100°C for 8 hours. After the reaction is completed, most of the dioxane and ammonia water are removed by rotary evaporation, and then the mixture is heated and dried under an oil pump for 3 hours to remove the residual hydrazine hydrate.
[0094] S3: Add 50 ml of 30% hydrogen peroxide to the polymer from which hydrazine hydrate has been removed, dissolve it by ultrasonication, and remove the hydrogen peroxide using a freeze dryer. The final yield is about 88%.
[0095] Molecular weight determination: The molecular weight of the water-soluble polymer was determined to be 1143 and the molecular weight distribution (PDI) was 1.079 using a room temperature gel permeation chromatography (GPC) apparatus (Agilent 1260) (manufactured by Agilent Technologies, Inc.) and a column (PLgei 5μm MIXED-C 300*7.5mm) (manufactured by Agilent Technologies, Inc.). Column temperature: 50°C, eluent: water, flow rate: 1.0 ml / min, standard sample for calibration curve preparation: polyethylene glycol. The molecular weight of the water-soluble polymer was determined to be 1143 and the molecular weight distribution (PDI) was 1.079.
[0096] Example 6
[0097] S1: Chain transfer agent 4-morpholine dithiocarboxylic acid cyanoethyl ester (C-1, 10mmol, 2.013g) and free radical initiator azobisisobutyronitrile (AIBN, 1.25mmol, 205mg) were added to the reaction bottle, and then nitrogen was replaced three times. Then, solvent dioxane (33mL) and polymerization monomer N-vinylpyrrolidone (A-5, 125mmol, 13.36g) were added, and nitrogen was replaced three times. After that, it was heated to 70°C under nitrogen atmosphere. The polymerization time was 7h. After the reaction was completed, the temperature was lowered and the nitrogen protection was removed. It was stirred for 1h under air atmosphere to quench the free radicals.
[0098] S2: The polymer synthesized above is dissolved in a solvent having a volume ratio of 1:2 of dioxane and hydrazine hydrate, and then refluxed at 100°C for 8 hours. After the reaction is completed, most of the dioxane and ammonia water are removed by rotary evaporation, and then the mixture is heated and dried under an oil pump for 3 hours to remove the residual hydrazine hydrate.
[0099] S3: Add 50 ml of 30% hydrogen peroxide to the polymer from which hydrazine hydrate has been removed, dissolve it by ultrasonication, and remove the hydrogen peroxide using a freeze dryer. The final yield is about 76%.
[0100] Molecular weight determination: The molecular weight of the water-soluble polymer was determined to be 984 and the molecular weight distribution (PDI) was 1.101 using a room temperature gel permeation chromatography (GPC) apparatus (Agilent 1260) (manufactured by Agilent Technologies, Inc.) and a column (PLgei 5μm MIXED-C 300*7.5mm) (manufactured by Agilent Technologies, Inc.). Column temperature: 50°C, eluent: water, flow rate: 1.0 ml / min, standard sample for preparing the calibration curve: polyethylene glycol. The molecular weight of the water-soluble polymer was determined to be 984 and the molecular weight distribution (PDI) was 1.101.
[0101] Example 7
[0102] S1: Chain transfer agent cyanomethyl-N-methyl (4-pyridine) aminodithiocarboxylate (C-12, 7.5mmol, 1.674g) and free radical initiator azobisisobutyronitrile (AIBN, 1.25mmol, 205mg) were added to the reaction bottle, and then nitrogen was replaced three times. Then, solvent dioxane (33mL) and polymerization monomer N-vinylpyrrolidone (A-5, 125mmol, 13.36g) were added, and nitrogen was replaced three times. After that, it was heated to 70°C under nitrogen atmosphere. The polymerization time was 7h. After the reaction was completed, the temperature was lowered and the nitrogen protection was removed. It was stirred for 1h under air atmosphere to quench the free radicals.
[0103] S2: The polymer synthesized above is dissolved in a solvent having a volume ratio of 1:2 of dioxane and hydrazine hydrate, and then refluxed at 100°C for 8 hours. After the reaction is completed, most of the dioxane and ammonia water are removed by rotary evaporation, and then the mixture is heated and dried under an oil pump for 3 hours to remove the residual hydrazine hydrate.
[0104] S3: Add 50 ml of 30% hydrogen peroxide to the polymer from which hydrazine hydrate has been removed, dissolve it by ultrasonication, and remove the hydrogen peroxide using a freeze dryer. The final yield is about 85%.
[0105] Molecular weight determination: The molecular weight of the water-soluble polymer was determined to be 1650 and the molecular weight distribution (PDI) was 1.075 using a room temperature gel permeation chromatography (GPC) apparatus (Agilent 1260) (manufactured by Agilent Technologies, Inc.) and a column (PLgei 5μm MIXED-C 300*7.5mm) (manufactured by Agilent Technologies, Inc.). Column temperature: 50°C, eluent: water, flow rate: 1.0 ml / min, standard sample for calibration curve preparation: polyethylene glycol. The molecular weight of the water-soluble polymer was determined to be 1650 and the molecular weight distribution (PDI) was 1.075.
[0106] Example 8
[0107] S1: Chain transfer agent cyanomethyl-N-methyl (4-pyridine) aminodithiocarboxylate (C-12, 5mmol, 1.117g) and free radical initiator azobisisobutyronitrile (AIBN, 1.25mmol, 205mg) were added to the reaction bottle, and then nitrogen was replaced three times. Then, solvent dioxane (33mL) and polymerization monomer N-vinylpyrrolidone (A-5, 125mmol, 13.36g) were added, and nitrogen was replaced three times. After that, it was heated to 70°C under nitrogen atmosphere. The polymerization time was 7h. After the reaction was completed, the temperature was lowered and the nitrogen protection was removed. It was stirred for 1h under air atmosphere to quench the free radicals.
[0108] S2: The polymer synthesized above is dissolved in a solvent having a volume ratio of 1:2 of dioxane and hydrazine hydrate, and then refluxed at 100°C for 8 hours. After the reaction is completed, most of the dioxane and ammonia water are removed by rotary evaporation, and then the mixture is heated and dried under an oil pump for 3 hours to remove the residual hydrazine hydrate.
[0109] S3: Add 50 ml of 30% hydrogen peroxide to the polymer from which hydrazine hydrate has been removed, dissolve it by ultrasonication, and remove the hydrogen peroxide using a freeze dryer. The final yield is about 88%.
[0110] Molecular weight determination: The molecular weight of the water-soluble polymer was determined to be 2060 and the molecular weight distribution (PDI) was 1.082 using a room temperature gel permeation chromatography (GPC) apparatus (Agilent 1260) (manufactured by Agilent Technologies, Inc.) and a column (PLgei 5μm MIXED-C 300*7.5mm) (manufactured by Agilent Technologies, Inc.). Column temperature: 50°C, eluent: water, flow rate: 1.0 ml / min, standard sample for calibration curve preparation: polyethylene glycol. The molecular weight of the water-soluble polymer was determined to be 2060 and the molecular weight distribution (PDI) was 1.082.
[0111] Effect Example
[0112] Comparative Example 1 is a sulfonic acid end group water-soluble polymer with a molecular weight of 3000; Comparative Example 2 is commercially available polyvinyl pyrrolidone (Boai Xinkaiyuan Medical Technology Co., Ltd.). The water-soluble polymers of the above embodiments 1-8 and the above comparative examples 1-2 are added to the grinding composition respectively, and the material is polished. The grinding composition also includes water, silicon dioxide abrasive particles, and sodium hydroxide, and the pH range of the grinding composition is between 8 and 11. Among them, the content of embodiments 1-8 and comparative examples 1-2 in the grinding composition is 0.05%.
[0113] The test machine is Ebara; the flow rate of the polishing composition is 300mL / min; the polishing pad is DH3110 (produced by Hubei Dinghui Microelectronics Materials Co., Ltd.), the dressing plate is DK1800 (Dinglong Huida), P / C downforce 6lbf, Head & Platen RPM: 93 / 87; the wafer used is Poly Blank wafer Thickness SiN Blank waferThickness
[0114]
[0115] The grinding rate is calculated by measuring the grinding removal amount at different positions of the wafer within a certain polishing time, and the measuring tool is NanoSpec II. The defectivity is the count of defects on the wafer and whether there are arc scratches, and the instrument used is KLA-TencorSP2 analyzer.
[0116] Table 1 Effects of Chemical Mechanical Polishing Compositions Examples 1-8 and Comparative Examples 1-2
[0117]
[0118]
[0119] As can be seen from the table, compared with comparative examples 1-2, the polishing rate of polysilicon / silicon nitride in examples 1-8 is relatively large, and the product defects are less, among which example 1 is the most preferred. Therefore, after adding the water-soluble polymer with sulfonic acid end groups in this example, the polishing effect of the grinding composition is significantly improved; at the same time, when the molecular weight of the water-soluble polymer with sulfonic acid end groups provided by the present application is between 800-2000, the polishing effect of the grinding composition is also better.
[0120] Although the implementation scheme of the present application has been disclosed as above, it is not limited to the applications listed in the specification and implementation scheme. It can be fully applicable to various fields suitable for the present application. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present application is not limited to the specific details and the implementation schemes shown and described herein.
Claims
1. A water-soluble polymer, characterized in that Its general structure is shown below: Among them, R1 is at least one of a hydrogen group, a cyanoethyl group, and an isobutylcyano group; R2 and R3 are each independently at least one of a hydrogen group, an alkyl group, an alkoxy group, an ester group, a carboxylic acid, an amide, and an aromatic ring; and n is any natural number.
2. The water-soluble polymer according to claim 1, characterized in that At least one of the R2 and the R3 has at least one of a methacrylate group, an acrylate group, a styrene group, and a pyrrolidone group.
3. The water-soluble polymer according to any one of claims 1 or 2, characterized in that The molecular weight of the water-soluble polymer is preferably in the range of 800-2000.
4. The water-soluble polymer according to any one of claims 1 or 2, characterized in that The water-soluble polymer is obtained by a solution consisting of a polymerization monomer, a chain transfer agent, an initiator and a solvent undergoing a polymerization reaction at a first preset temperature and a first preset time; then adding a reducing agent for a reduction reaction, reacting at a second preset temperature and a second preset time; and then adding an oxidant for an oxidation reaction; Wherein, the first preset temperature and the second preset temperature are both in the range of 60°C-120°C, and the first preset time and the second preset time are both in the range of 6h-12h.
5. The water-soluble polymer according to claim 4, characterized in that The R2 and R3 are both derived from the polymerized monomer, and the general structural formula of the polymerized monomer is The R1 comes from the chain transfer agent, and the general structural formula of the chain transfer agent is Wherein, Z is at least one of an alkyl group, an aryl group, an aralkyl group, a sulfanyl group, an alkoxy group, an aryloxy group, and an amino group; after the polymerization reaction is completed, a first polymer is obtained, and the general structural formula of the first polymer is The initiator is a free radical polymerization thermal initiator, including but not limited to an organic peroxide initiator, an azo initiator and a redox initiator.
6. The water-soluble polymer according to claim 4, characterized in that The molar ratio of the polymerization monomer, the chain transfer agent and the initiator is 100:1:0.1-100:20:
10.
7. The water-soluble polymer according to claim 4, characterized in that After the reduction reaction is completed, a second polymer is obtained, and the general structural formula of the second polymer is The molar ratio of the reducing agent to the solvent is 10:1-100:1, and the molar ratio of the oxidizing agent to the chain transfer agent is 10:1-100:
1.
8. A method for preparing a water-soluble polymer, characterized in that: The preparation method comprises the following steps: S1: A solution consisting of a polymerizable monomer, a chain transfer agent, an initiator and a solvent undergoes a polymerization reaction at a first preset temperature and within a first preset time; S2: adding a reducing agent, and reacting at a second preset temperature and within a second preset time; S3: adding an oxidant to obtain the water-soluble polymer according to any one of claims 1 to 7; Wherein, the general structural formula of the chain transfer agent is Z is at least one of an alkyl group, an aryl group, an aralkyl group, a sulfanyl group, an alkoxy group, an aryloxy group, and an amino group; R1 is at least one of a hydrogen group, a cyanoethyl group, and an isobutylcyano group; the general structural formula of the polymerizable monomer is: R2 and R3 are each independently at least one of an alkyl group, an alkoxy group, an ester group, a carboxylic acid, an amide, and an aromatic ring. The first preset temperature and the second preset temperature are both in the range of 60-120°C. The first preset time and the second preset time are both in the range of 6-12h.
9. The preparation method according to claim 8, characterized in that: At least one of the R2 and the R3 has at least one of a methacrylate group, an acrylate group, a styrene group, and a pyrrolidone group.
10. A polishing composition, characterized in that: The invention comprises abrasive particles, water, a pH regulator and the water-soluble polymer according to any one of claims 1 to 6.
Citation Information
Cited By
Preparation method and application of low-dispersity polymethyl methacrylate
CN121736160A
Process for the preparation of low-dispersion polymethyl methacrylate and its use
CN121736160B
